Contemporary Ostomy Care in Colostomy Patients: A Literature Review of Digital Health, Peristomal Skin Complications, and Quality of Life - Indah Susanti; Asmat Burhan (Indonesian Science Media, 2026)
Background: Colostomy care requires long-term self-management, peristomal skin protection, leakage prevention, and psychosocial adaptation. Digital health has emerged as a contemporary strategy to strengthen post-discharge support and improve quality of life among patients living with ostomy. Aim: To synthesize recent evidence on digital health, peristomal skin complications, and quality of life in colostomy care. Approach: This structured literature review included 10 core studies published from January 2021 to June 2026. PubMed/MEDLINE, Scopus, Web of Science, CINAHL, ScienceDirect, and Google Scholar were searched. Eligible studies involved adult ostomy patients and were synthesized narratively with methodological appraisal. Results: A total of 10 studies were included. Findings showed that telehealth, mobile applications, multimedia education, and continuous care improved self-care, self-efficacy, stoma adjustment, and quality of life. Peristomal skin complications remained common, with reported incidence ranging from 36.3% to 73.4%, mainly related to leakage and appliance problems. Conclusions: Contemporary colostomy care should integrate digital follow-up, nurse-led education, leakage prevention, peristomal skin protection, and psychosocial support to improve long-term outcomes. Implication for Nursing Practice: Nurses should use digital and face-to-face follow-up to strengthen self-care, detect complications early, prevent leakage, and support quality of life after colostomy